Indicadores fisiológicos e qualidade de cebolinha em sistema hidropônico com diferentes concentrações de sulfato de magnésio - Febraio, Ana Márcia de Oliveira (2021)
Chives are a popular culinary condiment, consumed fresh or processed by agribusinesses. Consumers are attracted by the integrity and quality of vegetables, characteristics linked to color intensity, aroma, nutritional composition, degree of sweetness and maturation, in addition to lesser susceptibility to degradation. The objective of this study was to monitor the physiological responses and quality attributes of the scallions (Allium schoenoprasun), cultivar “Todo Ano”, in a hydroponic system, with different concentrations of magnesium sulfate. Knowing the essentiality of magnesium for plants, as a constituent of the chlorophyll molecule and enzymatic activator, the evaluated treatments consisted of additions of magnesium sulfate in the standard solution proposed by Furlani et al. (1999): T1 – original composition (0.4 g L-1), T2 – 5%, T3 – 10%, T4 –15% and T5 – 20% more than the original composition. The experiment was carried out in the Horticulture sector of the Federal Technological University of Paraná, Campus Dois Vizinhos, from October to November 2020. To determine the quality of fresh hydroponic chives, at harvest time, the colorat tributes and soluble solids were analyzed (ºBrix), the content of phenolic compounds, the titratable acidity, the pH, the pungency levels, inaddition to the reading of the relative chlorophyll index (IRC). The variables that make up the colorare luminosity (L*), hue (ºhue angle), chromaticity (C*) and chromaticity coordinates (a* and b*). The dose of 20% more magnesium sulfate in the nutrient solution resulted in the lightening of the plants, as evidenced by the higher value of L* (32.63). The addition of magnesium sulfate contributed to gains in the green hue with a tendency to yellow, demonstrated by the quadratic behavior of the ºhue angle. The negative values obtained in the a* coordinate represent the greater green content, while the positive values in the b* coordinate set the proportion of yellow. The relative chlorophyll index showed that there was an increasein the chlorophyll content and, consequently, in the green color of the plants. The highest chlorophyll value (586.37) was observed with the highest dose (20%) of magnesium sulfate. In addition, the highest dose also provided a higher degree of sweetness and maturation, with an increase in the soluble solids content. The doses evaluated significantly influenced the amount of bioactive compounds present in chives, with an increase of 50.6% in the phenoliccontent at a dose of 20%. The main organic acid present in chives is pyruvic acid and its concentration determines the pungency levels, which for the evaluated doses had an average content of 0.081 g 100 g-1, not differing significantly between treatments. Chives are considered a vegetable with low acidity, and the doses of magnesium sulfate did not influence the titratable acidity either, with an average value of 0.63 mEq 100 g -of fresh mass. The highest pH value (6.66) of the leaf extract was observed in the highest dose of magnesium sulfate in the nutrient solution. It was found that the addition of magnesium in the cultivation of hydroponic chives was beneficial under the conditions of the experiment, improving the visual appearance of the leaves to meet the quality standards that the consumer seeks in this vegetable.